2020
DOI: 10.1016/j.chempr.2020.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Small Molecule Drug Candidate for Selective NKCC1 Inhibition in Brain Disorders

Abstract: Summary Aberrant expression ratio of Cl − transporters, NKCC1 and KCC2, is implicated in several brain conditions. NKCC1 inhibition by the FDA-approved diuretic drug, bumetanide, rescues core symptoms in rodent models and/or clinical trials with patients. However, bumetanide has a strong diuretic effect due to inhibition of the kidney Cl − transporter NKCC2, creating critical drug compliance issues and health concerns. Here, we report the discovery of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(112 citation statements)
references
References 58 publications
3
109
0
Order By: Relevance
“…[65] (polyclonal rabbit antibodies by Kurihara, 1999, Moore-Hoon and Turner, 1998, and Kaplan, 1996, (5), and (7), respectively). However, this staining pattern has been suggested to originate at least partially from satellite glia, which tightly surround the DRG neurons [66] (affinity-purified rabbit polyclonal antibodies by McDaniel and Lytle, 1999, andDel Castillo, 2005, antigens (1) and (4), respectively, and nucleotide (11) in Figure 2), ref. [67] (T4, antigen (6) in Figure 1).…”
Section: Nkcc1 Functions Outside the Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…[65] (polyclonal rabbit antibodies by Kurihara, 1999, Moore-Hoon and Turner, 1998, and Kaplan, 1996, (5), and (7), respectively). However, this staining pattern has been suggested to originate at least partially from satellite glia, which tightly surround the DRG neurons [66] (affinity-purified rabbit polyclonal antibodies by McDaniel and Lytle, 1999, andDel Castillo, 2005, antigens (1) and (4), respectively, and nucleotide (11) in Figure 2), ref. [67] (T4, antigen (6) in Figure 1).…”
Section: Nkcc1 Functions Outside the Cnsmentioning
confidence: 99%
“…During the second postnatal week in rats and mice [4] and around the time of full-term birth in humans [8,9], KCC2 is upregulated, leading to a decrease in neuronal intracellular chloride concentration ([Cl − ] i ) and a shift towards more hyperpolarizing GABAergic responses. NKCC1 is currently gaining increased attention as a possible therapeutic target for treating a myriad of CNS disorders [10], and the search for brain-permeable and specific NKCC1 drugs is heating up [11][12][13]. However, a major caveat here is that our understanding of the spatiotemporal expression patterns of NKCC1 in the brain is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…39–43 Recently, Hampel et al described Azosemide as a more potent inhibitor of human NKCC1, 44 and Savardi et al identified a new compound, ARN23746, that modestly inhibits NKCC1 function (30% at 10 uM and 95% at 100 uM), but had no effect on NKCC2. 45 …”
Section: Pharmacologymentioning
confidence: 99%
“…has now discovered a new drug candidate, termed ARN23746, which active selectively for NKCC1 in vivo versus NKCC2 [10].…”
Section: Nkcc In Vascular Cellsmentioning
confidence: 99%